Transcriptomic profile of TNFhigh MAIT cells is linked to B cell response following SARS-CoV-2 vaccination - Marzano, Paolo; Balin, Simone; Terzoli, Sara; Della Bella, Silvia; Cazzetta, Valentina; Piazza, Rocco; Sandrock, Inga; Ravens, Sarina; Tan, Likai; Prinz, Immo; Calcaterra, Francesca; Di Vito, Clara; et al. (Frontiers in Immunology, 2023)
Introduction: Higher frequencies of Mucosal-associated invariant T (MAIT) cells were associated with an increased adaptive response to mRNA BNT162b2 SARS-CoV-2 vaccine, however, the mechanistic insights into this relationship are unknown. Here, we hypothesized that the TNF response of MAIT cells supports B cell activation following SARS-CoV-2 immunization. Methods: To investigate the effects of repeated SARS-CoV-2 vaccinations on the peripheral blood mononuclear cells (PBMCs), we performed a longitudinal single cell (sc)RNA-seq and scTCR-seq analysis of SARS-CoV-2 vaccinated healthy adults with two doses of the Pfizer-BioNTech BNT162b2 mRNA vaccine. Collection of PBMCs was performed 1 day before, 3- and 17-days after prime vaccination, and 3-days and 3-months following vaccine-boost. Based on scRNA/TCR-seq data related to regulatory signals induced by the vaccine, we used computational approaches for the functional pathway enrichment analysis (Reactome), dynamics of the effector cell-polarization (RNA Velocity and CellRank) and cell-cell communication (NicheNet). Results: We identified MAIT cells as an important source of TNF across circulating lymphocytes in response to repeated SARS-CoV-2 BNT162b2 vaccination. The TNFhigh signature of MAIT cells was induced by the second administration of the vaccine. Notably, the increased TNF expression was associated with MAIT cell proliferation and efficient anti-SARS-CoV-2 antibody production. Finally, by decoding the ligand-receptor interactions and incorporating intracellular signaling, we predicted TNFhigh MAIT cell interplay with different B cell subsets. In specific, predicted TNF-mediated activation was selectively directed to conventional switched memory B cells, which are deputed to high-affinity long-term memory. Discussion: Overall, our results indicate that SARS-CoV-2 BNT162b2 vaccination influences MAIT cell frequencies and their transcriptional effector profile with the potential to promote B cell activation. This work also provides a blueprint for the promising use of MAIT cells as cellular adjuvants in mRNA-based vaccines.